Effect of thermal treatment on physical properties of Malaysian dolomitic limestone - Che Abdullah, Che Azurahanim; Albert, Emmellie Laura; Gee, Een Lau; Mohd Yusoff, Mohd Zaki; Abu Zarin, Mazni (Electroactive Materials Society, 2022)
Thermal treatment of dolomite powder from Kangar (northern region of Malaysia) was carried out at temperatures ranging from 400–800 °C. The modifications that dolomite undergoes during thermal treatment have been investigated using X-ray diffraction patterns (XRD). Additionally, Fourier Transform Infrared (FTIR) spectroscopy and Field Emission Scanning Electron Microscopy were used to discuss the results (FESEM). The XRD data, analysed using the X’Pert Highscore Plus application, revealed that as the heat treatment temperature was increased, the crystallinity degree and crystallite size decreased progressively. XRD analysis revealed that the samples are highly crystalline, consisting of two major phases: dolomite and calcium carbonate. After thermal treatment at 800 °C, the major phase of dolomite vanished, revealing a higher Ca(OH)2 content. FTIR spectral analysis determined that the primary component of dolomite is a carbonate mineral and that the primary characteristic bands of dolomite are located between 872 and 876 cm-1. FESEM analysis revealed the presence of discrete grains with preferential orientation, whereas post-thermal treatment completely destroyed the dolomite's original particle shape, resulting in the formation of smaller spherical particles consistent with the XRD data. The findings may pave the way for a better understanding of the phenomena that occur during dolomite thermal treatment, the changes in their physical properties, and their potential applications in a variety of bio-related commercial industries.